An analysis of the causes of savings and loan association failures - Benston, George J.; Salomon Brothers Center for the Study of Financial Institutions (New York, N.Y. : Salomon Brothers Center for the Study of Financial Institutions, Graduate School of Business Administration, New York University, 1985)
This book examines the reasons for the failures of savings and loan association in the United States. It also considers the direct investment, their risk and return, growth and the role of the Federal Home Loan Bank Board.
Includes bibliographical references: p. 178-180.
usc 25/09/2017
Loans
Keywords: Savings and loan associations; Business failures; Bankruptcy; United States